P177 Cost effectiveness of ambulatory management of spontaneous pneumothorax. (12th November 2015) - Pillay, C; Shah, B; Naeem, M; Reddy, R
Abstract : Introduction: Hospital admissions due to a primary diagnosis of spontaneous pneumothorax (SP) have an annual incidence of 11.2 per 100000. 1 It is estimated there are around 7200 emergency hospital admissions annually for pneumothorax in NHS. We have previously demonstrated pneumothorax patients requiring intercostal drains can be managed safely as outpatients with a Pneumostat device (similar to Heimlich valve). 2 Methods: All patients with primary spontaneous pneumothorax (PSP) and secondary spontaneous pneumothoraces (SSP) with a good performance status (WHO scale of 0–1) requiring an intercostal drain were eligible for outpatient management. SP patients presenting to hospital between July'14 and June'15 were analysed to see what percentage could be managed on the ambulatory pathway. The number of bed days saved was calculated from the total number of days patients spent in the community with the chest drain. The savings were then extrapolated to whole of NHS. Results: 50 episodes (in 44 patients) of SP presented to hospital between July'14 and June'15. 36 episodes required a chest drain insertion. 20 of these 36 episodes (55%) were managed on the ambulatory pathway. Based on this approximately 4000 (55% of total NHS admissions) SP patients could be managed in an ambulatory setting annually across NHS. The health care usage (number of attendances at ambulatory care, Chest X-rays and Pneumostat devices used) of patients managed on the ambulatory pathway is listed in table 1 . The unit cost of healthcare usage was obtained from the hospital information department and the overall cost of ambulatory care was calculated. The difference between this and the calculated bed day savings established the overall cost savings (Table 1 ). The potential savings to NHS equate to around £2.8 million based on the calculated average savings of £703/patient. Conclusion: Ambulatory management of Spontaneous pneumothorax could realise significant savings to the NHS. References: 1 Gupta D, Hansell A, Nichols T, et al . Epidemiology of pneumothorax in England. Thorax 2000;55 (8):666–671 2 Thomas K, Naeem M, Reddy RV. In the pleural zone: P173 ambulatory management of spontaneous pneumothorax. Thorax 2014;69 (Suppl 2):A150–A151